Answer:
[tex]\frac{4}{7}[/tex]
Step-by-step explanation:
let x represent the denominator then x - 3 represents the numerator.
Increase the numerator by 1, that is x - 3 + 1 = x - 2
Increase the denominator by 3, that is x + 3, then fraction
[tex]\frac{x-2}{x+3}[/tex] = [tex]\frac{1}{2}[/tex] ( cross- multiply )
2(x - 2) = x + 3, that is
2x - 4 = x + 3 ( subtract x from both sides )
x - 4 = 3 ( add 4 to both sides )
x = 7
Thus original fraction is
[tex]\frac{7-3}{7}[/tex] = [tex]\frac{4}{7}[/tex]